Fragmentation in MAC IEEE 802.15.4 to Improve Delay Performance in Wireless Body Area Network - R.Badlishah, Ahmad; Nadia Wan Abdullah, W.A; Yaakob, N; Elshaikh Elobaid, M.; Asilah Yah, S; Zunaidi, I (2019)
A Medium Access Control (MAC) protocol plays a significant role in enhancing the performances of Wireless Body Area Network (WBAN). This technology is commonly implemented IEEE 802.15.4 standard that works under CSMA/CA protocol. In addition, WBAN deals with probability of high traffic occurrence due to collection bulk of medical data that are generated from several bio-sensors through a continuous monitoring of patient's health. This phenomenon could result to congestion in the network which may lead to increment in delay and packet loss that could collapse the network. The increment in these two performances could lead to wrongly diagnosed of the diseases as well as late in medical help. Hence, the proposed mechanism aimed to reduce the delay through fragmenting the packets by decrementing the slot time in MAC 802.15.4 protocol under different number of number nodes with constant packet size and bit rate. The performances of the proposed mechanism are measured in terms of delay and packet loss by using OMNeT++ simulator tool. Based on the collected results, the proposed mechanism has shown a promising result in reducing the delay which means that it has improved the network performance of WBAN.